Clinical Trial of Sinudrain Haft Bahr Solution for Symptom Management in Mild to Moderate COVID-19 - Hamid Chegni (Archives of Advances in Biosciences)
Introduction: The COVID-19 pandemic, caused by the coronavirus, has been declared a global health emergency by the World Health Organization (WHO). This virus primarily affects the respiratory system, and affordable treatments for mild to moderate cases are urgently needed. Sinudrain Haft Bahr, a solution with antiseptic properties, was evaluated for its potential to alleviate COVID-19 symptoms. Materials and Methods: A clinical trial was conducted on 61 COVID-19 patients at Taleghani Hospital, Tehran. After a medical evaluation and analysis of symptoms, participants were randomized 1:1 (intervention vs. control) using admission code parity. The intervention group received Sinudrain, while the control group received routine medications from the national protocol. The drug was administered by gargling the solution three times a day and spraying it inside the nose six times a day. Patients' clinical symptoms were monitored on the first, third, and fifth days.